SCREENING OF MAIZE GENOTYPES AGAINST SOUTHERN CORN LEAF BLIGHT - RAJESH SINGH; V. P. MANI; R. S. KHANDELWAL; LEKHA RAM; R. P. SRIVASTAVA (The Bioscan, 2014)
A study was carried out, involving 119 maize genotypes to identify, the new sources of resistance to ‘Maydis Leaf Blight’ under artificial epiphytotic condition at three locations viz, Almora, Nagenahalli and Varanasi for 12 years (1999-2011) with the help of three experiments. All the three experiments included separate sets of genotypes except 13 inbreds (CM-145, CM-141, CM-212, CM-126, V-341, V-336, V-348, V-342, V-273, V-346, V-335, V338 and V-25) which were common in II nd and IIIrd Experiments. The present study has helped in the identification of 41 resistant, 41 moderately resistant, 24 susceptible and 13 highly susceptible maize genotypes. Ten lines viz. V53, V 178, V 190, V 336, V 340, V 341, V 345, V 348, CM 104 and CM 145 showed high level of resistance, whereas inbred lines viz., V 49, CM 126, CM 127, CM 202 and CM 212 showed high level of susceptibility as they scored above 3.5 disease score across the environment. The maize inbred lines CM 145, V 341, V 336 and V 348 expressed its high level of resistance in all the three environments. It was also observed that average disease incidence was high in Nagenahalli than Almora and Varanasi thus indicating that isolates of Cochliobolus heterostrophus were more virulent at Nagenahalli than rest of two environments.